PRODUCTION OF FERMENTABLE SUGARS FROM WATERHYACINTH BY HIGH-TEMPERATURE DILUTE-ACID HYDROLYSIS METHOD - Masende, Z. P.; Katima, J. H. Y.; Masanja, E. (Tanzania Journal of Engineering and Technology, 2018)
Abstract